Influence of substrates, light, filter paper and pH on the sporulation of Cercospora sojina - Gomez, Diana Erica; Reis, Erlei Melo (Grupo Paulista de Fitopatologia, 2019)
Fungi require special substrates for their isolation, vegetative growth and sporulation. In experiments conducted in the laboratory, the influence of substrates, light, filter paper and pH on the sporulation of Cercospora sojina conidia, the causal agent of soybean frogeye leaf spot, was assessed. The media potato sucrose agar, V-8 agar, tomato extract agar, soybean leaf extract agar, soybean seed extract agar, soybean meal agar, soybean flour agar and wheat flour agar were tested, added on the surface, with and without filter paper and under two light regimes, with 12 h light at 25°± 2°C and in the dark. A triple factorial 8x2x2 (substrates x light/dark x with/without filter paper) design with four replicates was used. V-8 agar medium was employed and the pH was adjusted with HCl 0.1N or NaOH 0.1N before autoclaving to the values: 3, 4, 5, 6, 7 and 8, and the pH of V-8 agar medium is 6.7. The evaluation was done on the seventh day of incubation. Data underwent regression analysis. Sporulation was maximized on the agar media V-8, seed extract, oat flour, tomato extract, and potato sucrose in the presence of filter paper and 12h light. On V-8 medium, maximal sporulation was obtained with pH 6.7.